Kepastian Hukum bagi Pesantren dalam Pendirian Badan Usaha Pesantren: Analisis Undang-undang nomor 18 tahun 2019 tentang Pesantren - Abdillah, Ahmad Imaduddin; Hartana, Hartana; Iryani, Dewi (Tasyri' : Journal of Islamic Law, 2024)
Islamic boarding schools as institutions that grow and develop together with the community have the potential to empower the community through business entities. Community trust in Islamic boarding schools is the basic capital for Islamic boarding schools to be able to establish business entities that are oriented towards community empowerment. Business entities in Islamic boarding schools have been mentioned in Law No. 18 of 2019, however, in the implementation of the establishment of Islamic boarding school business entities, they still refer to previously existing regulations. On the other hand, the Islamic boarding school law states that Islamic boarding schools in their activities, including community empowerment through the establishment of business entities, must maintain the characteristics, uniqueness, ideals and character of Islamic boarding schools so that in this case there is a legal vacuum. In this research, researchers used the theory of legal certainty and the theory of development law. Method The research approach used is a normative juridical approach and the type of research is qualitative research. The sources of legal material for this research were obtained from primary and secondary data sources. Where the primary source material is legislation and ministerial regulations. Meanwhile secondary data sources were obtained from literature studies, from various books, journals, and the internet. The data collection technique in this research uses library study techniques. Based on the research results, the regulation of legal certainty for Islamic boarding schools in carrying out business entity activities is mentioned in Article 45 of Law No. 18 of 2019. However, in establishing and managing business entities in Islamic boarding schools, regulations need to be issued that regulate them. This is necessary so that Islamic boarding schools in carrying out business activities still maintain the characteristics, uniqueness, character and ideals of Islamic boarding schools in accordance with articles 4 and 8 of Law No. 18 of 2019 concerning Islamic boarding schools. so that legal certainty, development, renewal and empowerment of society through Islamic boarding school business entities can be realized.